Analisis Kompensasi, Stres dan Disiplin terhadap Kinerja Pegawai Kantor Pelayanan Pajak Pratama Tulungagung - Ardy Sukmono; Edy Swasono; Supriyono Supriyono (Universitas Islam Kadiri, 2020)
Tax revenue is currently one of the largest sources of state revenue, accounting for 80% of the state budget. The taxation system will not work without the role of tax service office employees in serving taxpayers. Therefore, the performance of the tax service office employees must be improved. This study aims to analyze the effect of compensation, work stress and work discipline on the performance of the Tulungagung Pratama Tax Office employees. This study uses a quantitative method by collecting questionnaire data and taking a population of all employees with the status of State Civil Servants of KPP Pratama Tulungagung as many as 93 people. Data analysis used SPSS Version 25 application in the form of Multiple Linear Regression Equation Analysis. Based on the research results, compensation and discipline have no significant effect on employee performance and work stress has a significant effect on the performance of the Tulungagung Pratama Tax Office employees. Simultaneously, compensation, work stress and discipline have a significant effect on the performance of the employees of the Tulungagung Pratama Tax Office.